Dr. Laura Hetzler — Deep Plane Facelift — Baton Rouge - Hetzler, Laura (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Laura Hetzler, practicing in Baton Rouge, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003252; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; baton rouge